Spiritual Communication in Achieving the Marital Harmony: The Rapo-rapoang Tradition in Bugis Community - Munirah, Rezky; Karnay, Sudirman; Maria, Jeany Fatimah; Kamaruddin, Kamaruddin; Darlis, Syamsul (JURIS (Jurnal Ilmiah Syariah), 2025)
The rapo-rapoang tradition is a series of pre-wedding processions for the Bugis people of South Konawe. This tradition becomes a medium for spiritual communication between understanding customs and Islamic law in formulating the goals of marriage, so this issue needs special attention in the study of maqāṣid al-sharī’ah. This research aims to reveal the practice of spiritual communication through the South Konawe Bugis wedding rapo-rapoang tradition from a maqāṣid al-sharī’ah perspective. This research is qualitative research with an empirical-normative approach which includes the results of observations and interviews with religious leaders, traditional leaders and community leaders and includes a literature review that is in synergy with this research. The results of the research show that the rapo-rapoang tradition is practiced through four stages, namely mental, physical and spiritual preparation, religious and traditional education, family deliberation and congratulatory prayer. Spiritual communication in the rapo-rapoang tradition is an effort to integrate previous community understanding (pappaseng to riolo) with the concept of Islamic teachings and convey it to prospective brides and grooms. The rapo-rapong tradition in practice is in line with the provisions of Islamic law. In fact, if this tradition is analyzed from a maqāṣid al-sharī’ah perspective, it is found to be a form of support for achieving the goals of Islamic marriage. Therefore, ijtihad regarding the concept of achieving the goals of Islamic marriage through certain traditions implemented by Muslim communities throughout the world needs attention, in order to preserve culture and traditions within the circle of Islamic sharia.